2018
DOI: 10.3389/fncel.2018.00487
|View full text |Cite
|
Sign up to set email alerts
|

NGF-Dependent Changes in Ubiquitin Homeostasis Trigger Early Cholinergic Degeneration in Cellular and Animal AD-Model

Abstract: Basal forebrain cholinergic neurons (BFCNs) depend on nerve growth factor (NGF) for their survival/differentiation and innervate cortical and hippocampal regions involved in memory/learning processes. Cholinergic hypofunction and/or degeneration early occurs at prodromal stages of Alzheimer’s disease (AD) neuropathology in correlation with synaptic damages, cognitive decline and behavioral disability. Alteration(s) in ubiquitin-proteasome system (UPS) is also a pivotal AD hallmark but whether it plays a causat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 202 publications
(309 reference statements)
1
9
0
Order By: Relevance
“…Cholinergic and dopaminergic neurotransmission is important for hippocampal-dependent synaptic plasticity and memory regulation [ 32 , 33 ]. For example, cholinergic hypofunction occurs at the prodromal stages of AD-associated cognitive decline [ 34 , 35 ]. Furthermore, the injection of a dopamine D1-receptor antagonist can block the novel object preference behavior in rodents [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cholinergic and dopaminergic neurotransmission is important for hippocampal-dependent synaptic plasticity and memory regulation [ 32 , 33 ]. For example, cholinergic hypofunction occurs at the prodromal stages of AD-associated cognitive decline [ 34 , 35 ]. Furthermore, the injection of a dopamine D1-receptor antagonist can block the novel object preference behavior in rodents [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Basic forebrain cholinergic neurons (BFCNs) have an important role in learning, memory, and cognitive function [ 12 ]. Their survival and differentiation depend on nerve growth factor (NGF) and dominate cortical and hippocampal areas involved in memory and learning processes [ 13 ]. The hippocampus is a brain region rich in nicotinic acetylcholine receptors (NACHR), particularly the α7 subtype [ 14 ].…”
Section: Physiological Function Of Cholinergic Systemmentioning
confidence: 99%
“…In cellular and animal models of AD, NGF-dependent changes in ubiquitin-homeostasis trigger early cholinergic degradation. In an in vitro model of a septal hippocampal neuron rich in cholinergic energy, it is found that damage to the NGF/TrkA signaling pathway triggers a “death” degradation process that occurs before cell death, and NGF tightly controls excitatory neurotransmission in vitro through ubiquitination mediated pathways, accompanied by loss of specific vesicle transporters [ 13 ]. The endocannabinoid system regulates emotional learning and memory through the CB1 receptor and has been found to be unregulated in AD.…”
Section: Ad Relation To the Cholinergic Systemmentioning
confidence: 99%
“…The UPS is only responsible for the local degradation of a subset of synaptic proteins, and its function is regulated by synaptic activity or neural growth factors (NGF) to adjust the concentration of proteins important for synaptic function. This activitydependent or NGF-dependent UPS function can thereby feedback to regulate neurotransmitter release and synapse elimination [206,254,372,422].…”
Section: Tau As a Linker Between Cme Vesicle Trafficking And The Cytoskeletonmentioning
confidence: 99%